1254. Outbreak of Mycobacterium chelonae Skin Infections Associated With Human Chorionic Gonadotropin Injections at Weight Loss Clinics. (26th November 2018) - Mody, Rajal; Rainbow, Jean; Ferguson, Beth; Wiberg, Cody; Kupferschmidt, Trudy; Horn, Liz; Walters, Maroya Spalding; Fagan, Ryan; Chen, Greta; Rosenman, Karla
Abstract: Background: In December 2016, a dermatologist notified the Minnesota Department of Health (MDH) of three patients with skin lesions after self-administration of human chorionic gonadotropin (HCG) injections supplied by same weight loss clinic chain (Chain X); one lesion had been diagnosed as a nontuberculous mycobacteria (NTM) infection. We investigated to identify the etiology, determine contributing transmission factors, and to prevent additional cases. Methods: We defined a case as a skin or soft tissue lesion with a suspected infectious etiology in a Minnesota resident occurring within three months after HCG injection at or near an injection site. To find cases we sent health alerts to clinicians and clinical laboratories throughout Minnesota with diagnostic guidance, and we requested Chain X to notify all exposed patients. We visited two Chain X clinics to assess infection control practices, to collect invoices for product traceback, and to collect products for microbiological testing. All NTM isolates were identified by line probe assay and subtyped by pulsed-field gel electrophoresis (PFGE) at MDH. Results: We identified six cases with illness onset dates ranging from April to November 2016. All patients were adult women who did not share HCG vials. Four patients had clinical specimens that grew NTM; all isolates were identified as Mycobacterium chelonae that were indistinguishable by PFGE. Three patients with confirmed M. chelonae infection obtained HCG at Clinic A, and one from Clinic B, but sharing of reconstituted HCG by the two clinics could not be excluded. We identified several infection control breaches at both clinics including improper reconstitution of HCG and incorrect use of single use vials. The most likely source of the HCG was an unregistered out-of-state compounding pharmacy. Conclusion: This common source outbreak was likely due to contamination introduced either at a weight loss clinic or a compounding pharmacy. HCG injections are not US FDA-approved for weight loss, and their use may involve compounded products dispensed by alternative care settings that lack infection control expertise and regulatory oversight. This outbreak highlights the important role physician reporting of disease clusters plays in uncovering unsafe practices. Disclosures: All authors: No reported disclosures.